The impact of macroeconomic factors on the house prices during liberalisation - Ema Izati Zull Kepili (Penerbit Universiti Kebangsaan Malaysia, 2020)
The objective of the research is to investigate the impact of macroeconomic variables on the prices of different house types during liberalisation. This research examines the long term relationship between the respective house prices and the macroeconomic variables of interest rate, house supply, and the amount of loan approved. The methods used in this research are the Johansen Cointegration Test and VECM co-integration analysis based on Malaysian data over 1999-2012. The findings suggest that the prices of house were cointegrated regardless of the type. A higher degree of liberalisation has led to an increase of house prices. The impact, however was on the terrace, semi-detached, and high-rise houses, rather on the price of detached houses/bungalows. The policy makers may need to relook into the policy of opening up the property sector to foreigners, as the finding suggest that it has had an impact on potential local terrace buyers, who are largely low- and middle-income earners.